Representasi Nilai Islam pada Desain Karakter Joko Samudro dalam Media Webtoon - Elfira Dwi Purwati; Alfian Candra Ayuswantana; Sri Wulandari (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
This research is driven by the scarcity of religious-themed visual media capable of engaging the younger generation, particularly through popular platforms such as Webtoon. The urgency of this study lies in the need for innovative proselytizing (dakwah) media that resonates with contemporary visual tastes without compromising historical substance. The primary focus of this research is the visualization of Islamic values in the character design of Joko Samudro, an adaptation of the youth of Sunan Giri. This study aims to present a religious figure that is aesthetically relevant for today's Muslim youth. The research method employed is descriptive qualitative with Roland Barthes' semiotic approach to deconstruct the sign system in the character's visualization. Data were collected through interviews with the managers of the Giri Kedaton historical site, topographical observations, and questionnaires distributed to 102 respondents. The results indicate that Islamic values such as amanah, siddiq, and fathanah are manifested through a blend of traditional-modern attire with an earth-tone color palette (brown and white) symbolizing spiritual purity. Semiotically, the symmetrical white udeng (headtie) denotes self-control, while the loose baju kurung represents Islamic simplicity. In conclusion, this design successfully integrates historiographic identity with contemporary semi-realist visual trends, making the character of Joko Samudro an effective instrument for social meaning-making among the younger generation